(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2021)
This research aimed to describe: 1) the implementation of learning while learning from home during the Covid-19 epidemic; 2) a form of cooperation between students and teachers during online learning during the Covid-19 pandemic at SD STKIP Muhammadiyah Bangka Belitung; and 3) factors that hinder the establishment of cooperation between teachers and students during online learning. This research is a qualitative research using a qualitative exploratory research design. The primary data sources of this study were teachers of class IVA and IVB, parents of students, and students of SD STKIP Muhammadiyah Bangka Belitung and the secondary data sources of this study were articles of relevant research results and other related references. This research data collection using in-depth interview techniques, questionnaires, direct observation, documentation, and archival records. The data analysis of this study used the Miles and Huberman analysis technique in 3 stages, namely data reduction, data presentation, and drawing conclusions. The results of data analysis show: 1) The pattern of learning implementation at SD STKIP Muhammadiyah Bangka Belitung during learning from home during the Covid-19 period was virtual and door to door face-to-face. 2) Cooperation between teachers and students is quite good during online learning based on 3 indicators: attendance on time, respect teacher and peer opinions, and complete assignments on time. 55% of students who attend on time during online learning. Students who value / listen to their friends’ opinions when learning use zoom as much as 79%, and students who always submit assignments to the teacher on time as much as 48%. 3) factors that hinder the establishment of cooperation between teachers and students during online learning, namely: student enthusiasm, learning facilities and infrastructure, the role and competence of parents, and practicum-based subjects.